Implementation of physiotherapeutic shares in the prevention of diabetes complications in a Family Health Strategy - Freire, Ana Paula Coelho Figueira [UNESP]; Palma, Mariana Romanholi [UNESP]; Lacombe, João Carlos Aranha; Martins, Rodolpho Mauricio Leonardo; Lima, Renata Aparecida De Oliveira; Pacagnelli, Francis Lopes (Pontifícia Universidade Católica do Paraná, 2015)
Introduction In the Family Health Strategy (FHS), the treatment of Diabetes Mellitus (DM) includes education and lifestyle change strategies. Physiotherapists have a key role in this health setting. Objectives To implement actions of evaluation and guidelines for patients with type 2 DM who attend a Family Health Strategy (FHS), regarding diabetic foot and the practice of regular physical exercise in the control and prevention of the complications of Diabetes Mellitus. Methods 17 individuals from an FHS were evaluated, with the following procedures: clinical and anthropometric parameters, inspection, a questionnaire on diabetic neuropathy, tests of vibratory and tactile sensitivity, muscle function, range of motion, functional analysis, questions about exercise practice and guidance regarding controlling blood glucose and foot care. Results Deformities, dry skin, calluses, dehydration, ulceration, cracking and brittle nails were found. Peripheral neuropathy was not observed; tactile sensitivity was altered in the heel region and the vibratory sense was absent in 5% of individuals. A decrease in functionality of ankle movements was verified. Of the participants, 76% were sedentary, 24% knew about the benefits of practicing regular exercise, 25% had undergone a medical evaluation prior to performing physical exercise and, of these, 25% were supervised by a qualified professional. Discussion The implementation of physiotherapy actions in diabetics from an FHS was important for highlighting the presence of risk factors for diabetic complications. Conclusions Individuals attending the FHS need more information and programs for the prevention of diabetic complications.

Introdução Na Estratégia da Saúde da Família (ESF) o tratamento do Diabetes Mellitus (DM) inclui estratégias de educação e modificação do estilo de vida. Os fisioterapeutas vêm desenvolvendo papel fundamental nesse novo cenário de saúde. Objetivos Implementar ações de avaliação e orientações para pacientes com DM tipo 2, quanto ao pé diabético e à prática regular de exercícios físicos no controle e na prevenção de complicações do DM, os quais frequentam uma Estratégia de Saúde da Família (ESF). Métodos Foram avaliados 17 indivíduos de uma ESF, com os seguintes procedimentos: verificação de parâmetros clínicos e antropométricos, inspeção, questionário sobre neuropatia diabética, teste da sensibilidade tátil e vibratória, função muscular, amplitude de movimento, análise funcional, questionamentos sobre realização de exercícios, orientações sobre sua prática no controle glicêmico e orientações quanto aos cuidados com os pés. Resultados Foram encontradas deformidades, pele ressecada, calos, desidratação, ulceração, rachaduras e unhas quebradiças. A investigação sobre neuropatia periférica não indicou sua presença; a sensibilidade tátil estava alterada principalmente na região do calcanhar e a sensibilidade vibratória estava ausente em 5% dos indivíduos. Verificou-se diminuição na funcionalidade em movimentos de tornozelo. Dos participantes, 76% eram sedentários e 24% conheciam os benefícios da prática regular de exercícios físicos; 25% dos indivíduos passaram por avaliação médica antes de realizar exercício físico, que era supervisionado por profissional habilitado em 25% dos casos. Discussão A implementação de ações fisioterapêuticas nos diabéticos de uma EFS foi importante para destacar a presença de fatores de risco para complicações do diabetes. Conclusões Os indivíduos da ESF necessitam de mais informações e programas para a prevenção de complicações do DM e apresentam alterações predisponentes a amputações e outras complicações.
Implementação de ações fisioterapêuticas na prevenção de complicações do diabetes na Estratégia de Saúde da Família
Keywords: Physical Therapy; Diabetes Mellitus; Family health; Diabetic foot; Diabetic neuropathies; Fisioterapia; Diabetes Mellitus; Saúde da família; Pé diabético; Neuropatias diabéticas